Surrealism in André Breton’s Autobiographical Story “Nadja” - Dručkutė, Genovaitė (Literatūra, 2017)
The object of the analysis is the autobiographical story “Nadja” (1928) by the French Surrealist writer and theoretician André Breton. As the story narrates the real events of the year 1926, it also inscribes the events that took place ten years ago. The research draws on the premise that André Breton uses a mental disorder as a foregrounding surrealist manifestation as it seeks a twofold aim: firstly, to analyze the quest of surrealist identity, and, secondly, to develop a surrealist perspective on a woman. The analysis draws on the theoretical postulates of surrealism as they are explicated by André Breton in “The Manifesto of Surrealism”; the research also relies on the feminist literary theory (Simone de Beauvoir), and literary criticism. The analysis confirms that, written by the end of the 1920s, the autobiographical narrative “Nadja” is a document of crisis. It reflects a certain stage in the identity search undertaken by the author and his fellow surrealists. An accidental acquaintance with a mysterious young woman, who, as it later turns out, is mentally ill, opens for Breton an authentic surrealist experience and disperses the doubts. In this way, the surrealist identity of the author of the narrative is reinforced and entrenched. It is concluded that in the book “Nadja” the history of the finite founding of surrealism is developed, in which a mental disorder plays a central role. Nadja, as she, against her will, partakes in Breton’s experiment, is bestowed the existence of an object rather than a subject.